2018
DOI: 10.13057/biodiv/d190102
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Falcataria moluccana and its relationship to the resistance of gall rust disease

Abstract: Lelana Ne, Wiyono S, Giyanto, Siregar IZ. 2018. Genetic diversity of Falcataria moluccana and its relationship to the resistance of gall rust disease. Biodiversitas 19: 12-17. The use of cultivars that are resistant to a particular disease is one strategy that could mitigate the incidence of gall rust disease on Falcataria moluccana. Previous studies on the genetic diversity of F. moluccana did not attempt to link that genetic diversity to gall rust disease resistance. This research was carried out using RAPD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
3
1
3
Order By: Relevance
“…The Ho, He and I value of resistant accession infested by gall rust disease were lower than the susceptible. The values were similar to those studied by Lelana et al (2018). A population is more susceptible to unfavorable environmental conditions if there is a lack of heterozygosity (Basyuni et al 2012) and genetic diversity for disease resistance in host populations is generally thought to reduce the risk of spread for infectious diseases (Lively 2010).…”
Section: Genetic Diversity Of Falcatria Moluccana Accessionssupporting
confidence: 74%
See 1 more Smart Citation
“…The Ho, He and I value of resistant accession infested by gall rust disease were lower than the susceptible. The values were similar to those studied by Lelana et al (2018). A population is more susceptible to unfavorable environmental conditions if there is a lack of heterozygosity (Basyuni et al 2012) and genetic diversity for disease resistance in host populations is generally thought to reduce the risk of spread for infectious diseases (Lively 2010).…”
Section: Genetic Diversity Of Falcatria Moluccana Accessionssupporting
confidence: 74%
“…The genetic diversity value also indicated that microsatellite primers used has a high ability to distinguish accessions. Expected heterozygosity values that varied from 0.431 to 0.623 in susceptible populations and 0.496 to 0.650 in resistant populations indicated polymorphism obtained with microsatellite marker was greater than those obtained in a previous study using RAPD by Siregar and Olivia (2013) ranged from 0.1328 to 0.2946 and Lelana et al (2018) ranged from 0.018 to 0.299. It implied that the usage of microsatellite marker is effective to gain higher polymorphism due to its co-dominant trait.…”
Section: Genetic Diversity Of Falcatria Moluccana Accessionscontrasting
confidence: 58%
“…(a) The amplified DNA of sengon using primer OPA-05, (b) The amplified DNA of sengon using primer OPA-14, and (c) The amplified DNA of sengon using primer OPY-16. higher mean of genetic diversity than the sengon half-sib progeny population (He = 0.244) analyzed with the RAPD marker by Rostini et al (2018) and genetic diversity of healthy-growing sengon populations (He = 0.262) in various locations on the Java Island which was analyzed by Lelana et al (2018) using the RAPD marker. This pattern indicated that sufficient of the diversity source in sengon from Solomon provenance that grows in Pompok Landak Permanent Nursery-Haurwangi Village at this time.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Skor tingkat keparahan penyakit dihitung dengan metode Lelana, Wiyono, Giyanto, & Siregar (2018) yang dimodifikasi. Skor tingkat keparahan penyakit dibedakan menjadi dua yaitu skor untuk tanaman berumur 1-2 tahun dan skor untuk tanaman yang berumur di atas 2 tahun.…”
Section: B Pengamatan Insidensi Dan Keparahan Penyakitunclassified